Mekanisme Transaksi E-Commerce Menurut Perspektif Ekonomi Syariah (Study Kasus Masyarakat Muslim Indonesia, Malaysia dan Singapura) - Jannah, Nisa Zahratul; Dwi, Septy Rahma; S, Syahpawi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In this modern era, technological developments have spurred changes in individual habits in carrying out buying and selling transactions. Currently the buying and selling model has progressed, which we know as online buying and selling, where when a buyer wants to buy an item no longer needs to come and meet face to face with the seller, just by using a gedjet and laptop, the item ordered will arrive. With the various conveniences available, many people choose to shop online on the grounds that they can save time and don't have to leave the house. However, there are some drawbacks and impacts for the real market. One of the impacts is that the market is starting to be empty of buyers. In some cases, there are shortcomings in online shopping, including the presence of sellers who are not trustworthy, so that the goods ordered do not match those in the picture. Sometimes the description of the item does not match the photo shown. Another case is that there is a buyer who is not trustworthy with his order, when he orders goods purchased using the COD payment method, after the goods arrive the buyer does not want to pay for them. This aims to analyze the e-commerce transaction mechanism according to perfective sharia economics. The results of the analysis concluded that in terms of technical transactions, whether in the form of buying and selling services or goods, if the goods are delivered in a reliable manner because they are non-digital, then e-commerce transactions can be analogous to buying and selling al-salam, which has been regulated since its inception. Islam through the Sunnah of the Prophet PBUH. The use of e-commerce in Indonesia is permitted as long as both parties understand each other. The development of the use of e-commerce has had a big influence on various countries, both locally and internationally, including Singapore, Indonesia and Malaysia.